2021
DOI: 10.1101/2021.04.26.441262
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A human brain vascular atlas reveals diverse cell mediators of Alzheimer’s disease risk

Abstract: The human brain vasculature is of vast medical importance: its dysfunction causes disability and death, and the specialized structure it forms—the blood-brain barrier—impedes treatment of nearly all brain disorders. Yet, no molecular atlas of the human brain vasculature exists. Here, we develop Vessel Isolation and Nuclei Extraction for Sequencing (VINE-seq) to profile the major human brain vascular and perivascular cell types through 143,793 single-nucleus transcriptomes from 25 hippocampus and cortex samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 152 publications
(291 reference statements)
3
49
0
Order By: Relevance
“…There is overwhelming evidence for cerebrovascular alterations in AD pathology and amyloid-β deposition around leptomeningeal vessels is a hall mark of cerebral amyloid angiopathy, occurring in almost all AD patients (Greenberg et al, 2020). Of interest, recent scRNAseq profiling of human brain vasculature from healthy and AD cerebral cortex showed that perivascular fibroblasts were significantly under-represented in the AD brain single cell data set (Yang et al, 2021; Figure 3B). This is in contrast to large increases in CNS fibroblast numbers after acute CNS injuries and in neuroinflammation, demonstrating a different response of perivascular fibroblasts in AD.…”
Section: The Meninges and Alzheimer's Diseasementioning
confidence: 99%
“…There is overwhelming evidence for cerebrovascular alterations in AD pathology and amyloid-β deposition around leptomeningeal vessels is a hall mark of cerebral amyloid angiopathy, occurring in almost all AD patients (Greenberg et al, 2020). Of interest, recent scRNAseq profiling of human brain vasculature from healthy and AD cerebral cortex showed that perivascular fibroblasts were significantly under-represented in the AD brain single cell data set (Yang et al, 2021; Figure 3B). This is in contrast to large increases in CNS fibroblast numbers after acute CNS injuries and in neuroinflammation, demonstrating a different response of perivascular fibroblasts in AD.…”
Section: The Meninges and Alzheimer's Diseasementioning
confidence: 99%
“…32 However, more recently, sequencing has revealed the hippocampus to have fewer pericytes than cortical tissue. 9 In three regions of mouse brain, coverage was approximately 80%, whereas in the spinal cord, pericyte coverage varied from 48% to 68%, depending on location. 79 An additional reason for differences in vessel coverage data is that pericyte coverage appears heterogeneous, dependent on subtype, which relates to vessel diameter.…”
Section: Loss Of Pericyte-endothelial Signaling and Bbb Breakdownmentioning
confidence: 98%
“…46 In addition, a large number of ADrelated genome-wide association study genes are found in vascular cells. 9 Evidence of BBB disruption has been found in postmortem tissue from patients with AD and cSVD. 28,31 In particular, patients with AD and APOE4 have increased deposition of the blood component fibrin(ogen) perivascularly, 31 suggestive of leakage.…”
Section: Clinical Evidence Of Bbb Disruption In Ad and Csvdmentioning
confidence: 99%
See 2 more Smart Citations